Copper‐Catalyzed N1 Coupling of 3‐Aminoindazoles and Related Aminoazoles with Aryl Bromides. Issue 4 (30th November 2021) - Cyr, Patrick; Joseph‐Valcin, Eve‐Marline; Boissarie, Patrick; Simoneau, Bruno; Marinier, Anne
Abstract: The N 1 ‐selective arylation of 3‐aminoindazoles using copper catalysis is herein reported. The reaction uses readily accessible aryl bromides as coupling partners, including those from heterocycles, and allows easy access to a broad variety of substituted 3‐aminoindazoles. The methodology was also examined on other aminoazoles of interest for the pharmaceutical industry. Abstract : A coupling between 3‐aminoindazoles and aryl bromides, selectively occurring at the N 1 position, was developed using copper catalysis. The transformation allows the use of a variety of heterocycles for both coupling partners and provides rapid access to arylated aminoazoles of high interest in drug discovery.